Conceituação, avaliação e promoção de automonitoria em pré-escolares e sua relação com competência social e comportamentos-problema - Dias, Talita Pereira (2014)
Currently, there is strong evidence that the promotion of social skills and social competence is crucial to quality of socio-emotional development and prevention of behavior problem from early childhood. The literature shows that both social skills and social competence depend, ultimately, on self-monitoring. However, there is a set of conceptual and methodological challenges associated with the analysis and promotion of self-monitoring, especially with young children. In the present study, it is proposed to; (1) define operationally the term self-monitoring, (2) analyze its relationship with social skills and behavior problem, and (3) develop a self-monitoring resource to evaluate and analyze the effects of an intervention that combined specific procedures to promote it. This thesis is composed of four chapters. In chapter I, a behavioral definition of indicators of self-monitoring is proposed based on literature review, considering the fields of Social Skills and of Behavior Analysis. In Chapter II, the stages of construction of Illustrative Resource of Self-monitoring (RIAM) for assessment (RIAM-A) and for intervention (RIAM - I) in preschoolers are described. In Chapter III, a study is presented with the objective of verifying similarities and differences in behavioral indicators of self-monitoring evaluated by RIAM-A (self-description, description and choice of consequence) of 53 children, between five and six years old, divided into three groups (socially competent, with deficits in social skills, and internalizing behavior problem and externalizing or mixed behavior problem). The results indicated that children with social skills were better than children with behavior problem in selfmonitoring tasks, further verifying positive correlation between self-monitoring scores and social skills scores, and a negative correlation between self-monitoring scores and internalizing behavior problem. Finally, Chapter IV examined the effects of an intervention involving contingency analysis training and exposure to social contingencies in structured situations to promote self-monitoring and its impact on social skills, social competence and reducing behavior problems in preschool evaluated by RIAM-A and who presented difficulties in self-monitoring tasks. Individual sessions were carried out, which included: presentation of interactive situations in the form of drawing, discussion about the appropriateness or relevance of each response and probable consequences, followed by participation in structured presentation of the demand for social skills discussed previously. The results showed that, relative to a comparison group, children who took part in intervention had improved social skills, self-monitoring and social competence, but not reduction of behavior problem. The set of studies suggests the feasibility of research on self-monitoring in early childhood, proposing indicators, resources and procedures for assessment and intervention strategies for self-monitoring. The implications of the research are discussed in terms of theoretical, methodological, empirical and practical contributions.